Efektivitas Kinesio taping dan Pelvic rocking exercise terhadap Penurunan Nyeri Punggung Ibu Hamil Trimester III di Puskesmas Kenali Besar Kota Jambi - Nuraidah, Nuraidah; Herinawati, Herinawati; Rosmaria, Rosmaria; Atika, Ghea; Iksaruddin, Iksaruddin (Universitas Baiturrahim, 2025)
Back pain often experienced by third trimester pregnant women can interfere with comfort and quality of life due to changes in posture, increased load, and hormonal changes. Appropriate treatments, such as kinesio taping and pelvic rocking exercise, are needed to relieve these complaints and improve the quality of life of pregnant women. This study aims to evaluate the effectiveness of kinesio taping and pelvic rocking exercise in reducing back pain in third trimester pregnant women at Kenali Besar Community Health Center, Jambi City. This study was a quasy-experiment study conducted in February-August 2022 at the Kenali Besar Health Center, Jambi City. The study population was all third trimester pregnant women at the Kenali Besar Health Center as many as 181 pregnant women. The research sample was third trimester pregnant women at the Kenali Besar Health Center as many as 46 pregnant women selected using purposive sampling technique. The research instrument used the Numerical Rating Scale NRS sheet. The dependent variable is back pain and the independent variable is the intervention (kinesio taping vs pelvic rocking exercise). Interventions include the provision of kinesio taping and pelvic rocking exercise. Kinesio taping was given 2 times a week and pelvic rocking exercise was given 3 times a week. Analysis using the T-Test test. Before the intervention, the average pain level of pregnant women in the kinesio taping group (mean = 2.8, SD = 3.4) and in the pelvic rocking exercise group (mean = 2.3, SD = 3.1). After the intervention, the average pain level of pregnant women in the kinesio taping group (mean = 1.7, SD = 2.5) and in the pelvix roxing exercise group (mean = 2.1, SD = 2.6), increased in the kinesio taping group and proved to be statistically significant. There is an effect of kinesio taping on reducing back pain in pregnant women. Puskesmas Kenali Besar Jambi City should consider applying these two methods in the health care program for pregnant women to improve their quality of life and comfort during pregnancy